Quantum Dynamics in Double-Well System with Polychromatic Perturbation Using Entangled Trajectory Molecular Dynamics Method (Journal of Atomic and Molecular Sciences, 2016)
We investigate quantum dynamics in a double-well system subject to time-dependentperturbation with some incommensurate frequencies using entangled trajectorymolecular dynamics method. We first compare time evolution of energy of thedriven system with two mode perturbation under classical dynamics with one underquantum dynamics, it is found that quantum dynamics obeys Ehrenfest's theorem andit shows our results obtain from entangled trajectory molecular dynamics method arecorrect and accurate. Quantum coherence suppresses trajectory which initial energyis higher than barrier to get over it, this process is named coherent destruction of tunneling(CDT). We show this interesting phenomenon through showing entangled trajectoryand corresponding classical trajectory in phase space and discuss their energyfluctuation with time. Furthermore, we discuss quantum dynamics with different frequencymode perturbation from the perspective of autocorrelation evolution, classicalchaos brings remarkable influence on quantum-mechanical phenomena.
Keywords: Entangled trajectory molecular dynamics method; Coherent destruction of tunneling; Classical chaos.